Corporate Governance Model of Islamic Philanthropy at Islamic Hospitals in Ponorogo - Luhur Prasetiyo; Unun Roudlotul Jannah; Nurma Fitrianna (Ekonomi Syariah IAIN Kudus, 2022)
This article aims to analyze the governance of ZISWAF in philanthropic institutions placed in hospitals. Hospitals are health facilities that are often not affordable for the underprivileged. Some cases of displaced patients because they do not have funds to get health services in hospitals often occur. Islamic philanthropy in hospitals is vital to address this issue. This research is qualitative, with the location of three hospitals in Ponorogo, namely RSU 'Aisyiyah, RSU Muhammadiyah, and RSU Muslimat. The informant of this study is the manager of Islamic philanthropy. In addition, data is also collected from recipient patients and donors. The results showed that Islamic philanthropy in the three hospitals was carried out by philanthropic institutions affiliated with community organizations. At 'Aisyiyah and Muhammadiyah Hospital, philanthropy is managed by the Lazismu Service Office. Meanwhile, at Muslimat Hospital, philanthropy is managed by JP-ZIS NU Care. Philanthropic governance in the three hospitals can be divided into two models: integrated Islamic philanthropy institution and external Islamic philanthropy institution.